A Family of Novel Exact Solutions to 2+1-Dimensional KdV Equation. (30th March 2014) - Wang, Zhen; Zou, Li; Zong, Zhi; Qin, Hongde
Abstract : We introduce two subequations with different independent variables for constructing exact solutions to nonlinear partial differential equations. In order to illustrate the efficiency and usefulness, we apply this method to 2 + 1 -dimensional KdV equation, which was first derived by Boiti et al. (1986) using the idea of the weak Lax pair. As a result, we obtained many new exact solutions.